Study of fluxing in Al refining process by rotary and crucible furnaces. Issue 1 (2nd January 2019) - Capuzzi, Stefano; Timelli, Giulio; Capra, Leonardo; Romano, Luca
Abstract: The process used to obtain recycled Al alloys depends on the scrap quality. Rotary furnaces are normally used in Europe as they allow a great productivity and they can process low quality scrap using a salt flux to protect the molten metal from oxidation. In this article, the effect of the quantity of salt on the metal recovery has been experimentally investigated by melting several types of scrap under a mixture of NaCl–KCl–Na3 AlF6 salts. The quantity of salt has been related to the salt factor (SF), which is the ratio between the non-metallic content in the scrap and the quantity of salt required. The same levels of salt factor have been tested by melting the scrap in rotary and crucible furnaces. The metal recovery increases with the salt content for both furnaces. The results obtained with the different melting processes are comparable because the yield difference is similar considering different salt factors. Crucible furnace gives greater metal recovery but it cannot replace rotary furnace in Al refining industry due to lower melting capacity. However, the results highlight that the optimisation of the Al refining process can be supported by preliminary tests through crucible furnaces reducing the time and material consumptions.